Event‐related potentials during sustained attention and memory tasks: Utility as biomarkers for mild cognitive impairment. Issue 1 (3rd July 2018) - Waninger, Shani; Berka, Chris; Meghdadi, Amir; Karic, Marija S.; Stevens, Kimberly; Aguero, Cinthya; Sitnikova, Tatiana; Salat, David H.; Verma, Ajay
Abstract: Introduction: The objective of the study is to validate attention and memory tasks that elicit event‐related potentials (ERPs) for utility as sensitive biomarkers for early dementia. Methods: A 3‐choice vigilance task designed to evaluate sustained attention and standard image recognition memory task designed to evaluate attention, encoding, and image recognition memory were administered with concurrent electroencephalography acquisition to elicit ERPs in mild cognitive impairment (MCI) and healthy cohorts. ERPs were averaged, and mean or maximum amplitude of components was measured and compared between and within cohorts. Results: There was significant suppression of the amplitude of the late positive potential in the MCI cohort compared with the healthy controls during 3‐choice vigilance task, predominantly over occipital and right temporal‐parietal region, and standard image recognition memory task over all regions. During standard image recognition memory task, diminished performance showed strong correlation with electroencephalography measurements. The old/new effects observed in the healthy controls cohort correlated with performance and were lost in MCI. Discussion: ERPs obtained during cognitive tasks may provide a powerful tool for assessing MCI and have strong potential as sensitive and robust biomarkers for tracking disease progression and evaluating response to investigative therapeutics. Highlights: Significant suppression of event‐related potential components and diminished performance during sustained attention and memory tasks are correlated in mild cognitive impairment patients compared with healthy, age‐matched controls. Mild cognitive impairment patients lose the recognition effect observed in healthy controls that reflects activation of neural circuits associated with memory. The data support use of cognitive tasks with concurrent electroencephalography as a biomarker for disease progression and as a pharmacodynamic end point for neurodegeneration clinical trials.